Turning back to traditional trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Pacific Islanders were once among the most self-sufficient and well-nourished peoples in the world, building their agricultural systems around a diverse base of local tree species